ChemInform Abstract: Reaction Mechanisms: Pericyclic Reactions. Issue 1 (January 2015) - Greer, Edyta M.; Cosgriff, Christopher V.
Abstract Review: a survey of articles on pericyclic reactions published in 2012; 45 refs.